2011
DOI: 10.1007/s10856-011-4517-y
|View full text |Cite
|
Sign up to set email alerts
|

Buffer-regulated biocorrosion of pure magnesium

Abstract: Magnesium (Mg) alloys are being actively investigated as potential load-bearing orthopaedic implant materials due to their biodegradability in vivo. With Mg biomaterials at an early stage in their development, the screening of alloy compositions for their biodegradation rate, and hence biocompatibility, is reliant on cost-effective in vitro methods. The use of a buffer to control pH during in vitro biodegradation is recognised as critically important as this seeks to mimic pH control as it occurs naturally in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 28 publications
5
50
0
Order By: Relevance
“…In fact, the comparison was actually substantially worse in the solution which contained proteins compared to the simpler SBF used (EBSS). A substantial increase in corrosion was also observed in a study by Kirkland et al [72] when 40 g L −1 of BSA was added to MEM, as presented in Fig. 3.…”
Section: Proteinssupporting
confidence: 80%
See 4 more Smart Citations
“…In fact, the comparison was actually substantially worse in the solution which contained proteins compared to the simpler SBF used (EBSS). A substantial increase in corrosion was also observed in a study by Kirkland et al [72] when 40 g L −1 of BSA was added to MEM, as presented in Fig. 3.…”
Section: Proteinssupporting
confidence: 80%
“…This result was supported by the study of Kirkland et al [72] where a minimal to slight difference was found between HBSS and EBSS when an active CO 2 buffer was used, as presented in Fig. 3.…”
Section: Increasing Concentrations Of Hcosupporting
confidence: 76%
See 3 more Smart Citations